MAJALAH DINDING SEBAGAI SARANA PENINGKATAN LITERASI SAINS SISWA SEKOLAH DASAR - Kui, Maria Goreti; Dinatha, Ngurah Mahendra; Gelu, Afrianus; Kua, Maria Yulian (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This research aims to improve students' reading literacy at UPTD SDI Waewaru through the implementation of science wall magazine media. The method used is Classroom Action Research (CAR) which consists of two cycles, where each cycle includes the stages of planning, implementation, observation, and reflection. The subjects of the study are 30 students selected as respondents. Data were collected using observations and tests in the form of multiple-choice questions to measure the students' reading literacy levels. The research results show a significant improvement in students' reading literacy after the implementation of the science wall magazine program. In the first cycle, as many as 20 students had a low reading literacy level. However, after the implementation of cycle II, the number decreased to only 8 students. This shows that the science wall magazine media is effective in improving students' reading literacy skills. The conclusion of this study is that the implementation of science wall magazines can be an effective solution to improve students' reading literacy in elementary schools. Therefore, this program is recommended as a learning medium that can be applied to support literacy improvement efforts in schools